Contribución al estudio de la caries dentaria en niños costarricenses - Pauly S., Raymond (1955)
A preliminary study of dental caries among children of San José, Costa Rica, is presented, based on present knowledge of the role of sugar in caries, and of the importance of its bacteriological diagnosis. Current methods for the latter are discussed, stressing the need for proper identification of Lactobacillus acidophilus colonies.Dextrose-broth and tomato-agar (pH 5) cultures, the most frequent methods for Lactobacillus counts, are not recommended for use in humid tropical regions; tomato-agar in particular is highly susceptible to contamination. Rogassa, or LBS, medium, on the other hand, proved satisfactory. Snyder's colorimetric method is recommended for determination at the clinic of the patient's susceptibility to caries, and as an auxilliary method in Lactobacillus counts. Cultures in peptonized milk are not recommended because of results disagreeing with those obtained by other methods. Cases studied were classified in four general categories according to the usual amount of sugar in the diet: I-Occasional: scanty, taken with meals as desserts, pastries, etc. II-Moderate: taken with meals, in beverages, cereals, desserts, etc. III-Frequent: taken with meals, in beverages, cereals, desserts, etc., and moderately between meals in ice cream, pastries, soft drinks, etc. IV-Exeessive: taken abundantly with meals and between meals, In excess in beverages, candy, soft drinks, pastries, etc. From the study of 107 cases, the following conclusions are derived: 1. The results support entirely the thesis that the etiologic factor in dental canes is sugar intake. 2. While the comparison of cases does not allow a statement that a given sugar intake results in a particular number of caries, in the majority of cases a certain general relation is seen to exist between the usual amount of sugar in the diet, the Lactobacillus count, and the number of cavities (Graph 1). A small number of cases were found in which the number of caries was either very high, or else very low, for the Lactobacillus count and the sugar intake reported (Graphs 1 and 2). 3. These deviations from the general trend are explained as the effect of a variety of factors: a) a certain immunity or resistance to caries exhibited by a number of individuals who develop no caries, or very few, even when sugar is included in the diet. The protective factor is known to be present in saliva, although the calcification and position of the teeth may also be important. b) Age, as the susceptible period is over short1y after twenty years. e) The time of taking the samples of saliva, as the counts are higher immediately after meals. 4. Two cases were found with no cavities. In one, an extremely low Lactobacillus count appeared to be one of the factors, and may correspond to an extremely low sugar intake, or else to a high natural resistance. In the other, the high Lactobacillus count justified the assumption that caries would develop in the near future. 5. The intake of sugar between meals appears to be more damaging than with meals. 6. Monosaccharides and disaccharides are the usual causative factors of caries, although in highly susceptible individuals there is also a certain action of polysaccharides. 7. The DMF índex is considerably high for Costa Rican children between 3 and 6 years; 14 between 7 and 10 years; and 20 between 11 and 16 years - which stresses the need for investigation o f sugar content in their usual diet, and for some solution of the problem of constant consumption of candy and pastry. The need for public education of these points is emphasized.